2001
DOI: 10.1128/jb.183.24.7381-7386.2001
|View full text |Cite
|
Sign up to set email alerts
|

Complementation of Cold Shock Proteins by Translation Initiation Factor IF1 In Vivo

Abstract: The cold shock response in both Escherichia coli and Bacillus subtilis is induced by an abrupt downshift in growth temperature and leads to a dramatic increase in the production of a homologous class of small, often highly acidic cold shock proteins. This protein family is the prototype of the cold shock domain (CSD) that is conserved from bacteria to humans. For B. subtilis it has been shown that at least one of the three resident cold shock proteins (CspB to D) is essential under optimal growth conditions as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
39
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 46 publications
(48 reference statements)
4
39
0
Order By: Relevance
“…It has been shown that the cellular defects resulting from a double deletion in the genes encoding cold shock proteins CspB and CspC in Bacillus subtilis can be complemented by heterologous expression of E. coli IF1 (244). This confirms the structural resemblance and functionality between IF1 and the cold shock proteins.…”
Section: Translation Initiation Factorsmentioning
confidence: 56%
“…It has been shown that the cellular defects resulting from a double deletion in the genes encoding cold shock proteins CspB and CspC in Bacillus subtilis can be complemented by heterologous expression of E. coli IF1 (244). This confirms the structural resemblance and functionality between IF1 and the cold shock proteins.…”
Section: Translation Initiation Factorsmentioning
confidence: 56%
“…It has also been shown that heterologous expression of IF1 from E. coli in a Bacillus subtilis cspB/cspC double deletion strain complemented the loss of the cold shock induced protein CspB in B. subtilis (the homolog of CspA in E. coli) [36]. This finding led to a conclusion that IF1 and cold shock proteins have overlapping functions [36] and they could have evolved from a common ancestor [37]. Recently, it was shown that IF1 and CspA preferentially stimulate translation at low temperatures without mRNA selectivity [38] and that cold shock induces a stoichiometric imbalance between initiation factors and ribosomes [39].…”
Section: Discussionmentioning
confidence: 99%
“…The CSD is highly conserved from bacteria to humans (15,39,40) and is involved in coupling transcription to translation (36). Only recently the CSDBase database was established (http: //www.chemie.uni-marburg.de/ϳcsdbase), which includes detailed information about the CSD (37).…”
mentioning
confidence: 99%
“…In B. subtilis, csp double-deletion strains show a variety of phenotypes, such as altered protein synthesis, aberrant nucleoid structure, cell lysis upon entry into the stationary growth phase, and impairment in sporulation (13,39). The latter two defects were shown to be cured by heterologous expression of translation initiation factor IF1 from Escherichia coli (36).…”
mentioning
confidence: 99%